2003
DOI: 10.1002/elps.200390174
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation and subspecies development of the giant panda as revealed by DNA fingerprinting

Abstract: Over the last 100 years giant pandas (Ailuropoda melanoleuca) have been separated into six completely isolated mountain ranges. DNA fingerprinting revealed different differentiation patterns in giant pandas, including early-stage, late-stage, recent divergence and recent genetic depression. A separation around 10 000 years ago resulted in highly significant differences in DNA fingerprints and morphological characteristics between Qinling and Sichuan populations. Supported by morphological differences, the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 19 publications
6
38
0
Order By: Relevance
“…However, they retain the digestive system of a carnivore, and thus derive little energy and little protein from the consumption of bamboo (Hu 2001;Wan et al 2003). Because the diet is low in nutrition, it is important for a wild giant panda to keep its digestive tract full.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, they retain the digestive system of a carnivore, and thus derive little energy and little protein from the consumption of bamboo (Hu 2001;Wan et al 2003). Because the diet is low in nutrition, it is important for a wild giant panda to keep its digestive tract full.…”
Section: Discussionmentioning
confidence: 99%
“…The panda population in these mountains has a unique distribution pattern and evolutionary history. They are different from the mainstream population of A. m. sichuanensis in morphology and molecular biology (Lu et al 2001;Loucks et al 2003;Wan et al 2003Wan et al , 2005Liu et al 2009). Nonetheless, the habits and diet of Qinling pandas are similar to the pandas in Sichuan.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…At the same time, Wan et al (2006) found relatively low numbers of alleles of the MHC class II DRB locus in giant pandas. However, Lu et al (2001) concluded that panda populations still retained considerable genetic diversity when compared against other carnivorous species, which was insured by Wan et al (2003). Fang et al (2002Fang et al ( , 2003 found the genetic variation in giant panda populations has a relationship with the number of individuals and that larger populations possessed relatively higher genetic variation than smaller populations.…”
Section: Introductionmentioning
confidence: 96%
“…DNA fingerprinting is a good marker system (Wan et al, 2004) for small populations and has revealed loss of genetic diversity Fang, 2002, 2003;Wan et al, 2003a), genetic variation between subpopulations (Fang et al, 2002a, and genetic differentiation (Wan et al, 2003b) of endangered animals. With a reliable genetic marker, detecting the loss of genetic diversity requires archival specimens.…”
Section: Introductionmentioning
confidence: 99%